Data for "Folding and deploying identical thick panels with spring-loaded hinges" - Yang, J; Zhang, Y; Chatzis, MN; You, Z (Elsevier, 2022)
This article provides supplementary information for the manuscript “Folding and Deploying Identical Thick Panels with Spring-loaded Hinges” (Yang et al. 2022), in which collision-free deployments of a multiple degree-of-freedom (DoF) system are realized by using elastic hinges. This article characterizes two important parameters of such hinges, namely, the spring stiffness and the damping coefficient. The spring stiffness was acquired through quasi-static measurement of torque. A test rig consisting of rotary tables and strain gauges was developed for this purpose. The damping coefficient of the hinge was acquired by analyzing the responses of five free-vibration tests on a rotational mass-spring system. The time history of the response was processed, followed by system identification through the state-space estimation. Apart from the properties of the elastic hinges, the other system properties that were used for the simulations and the physical prototypes in (Yang et al. 2022) were detailed in this article. With these parameters, deployments with and without collisions were demonstrated through videos (V1, V2, and V3).